Performance of the Revised Children’s Manifest Anxiety Scale in a Sample of Children and Adolescents from Poor Urban Communities in Cape Town - Boyes, Mark; Cluver, L. (Hogrefe Publishing, 2013)
The Revised Children’s Manifest Anxiety Scale (RCMAS) is regularly used with South African children, although its performance in this context has yet to be empirically evaluated. This study assessed the basic psychometric properties of the RCMAS using data collected in a large study examining the mental health of children and adolescents living in poor urban communities around Cape Town. Reliability of the full-scale was good, and the predicted relationships between anxiety, depression, PTSD, delinquency, age, sex, and somaticism scores offered evidence of construct validity. However, the reliabilities for the physiological, worry/oversensitivity, and concentration subscales were low, and confirmatory factor analysis revealed the hypothesized three-factor model did not adequately fit the data. Exploratory analyses suggested a four-factor solution consisting of social evaluation, worry, affective responses, and physiological symptoms/sleep disturbance factors. Further confirmatory research examining this four-factor structure is needed. Given the continued use of the RCMAS in South Africa, these findings provide an important first step in establishing its reliability and validity for use with South African youth; however, scores obtained on the three subscales should be interpreted with caution and further detailed psychometric evaluation of the RCMAS in South African samples is clearly required.